2009
DOI: 10.1007/s10397-009-0479-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of heavy menstrual bleeding associated with uterine leiomyoma with the levonorgestrel-releasing intrauterine system

Abstract: Heavy menstrual bleeding is an increasingly common health problem. The levonorgestrel-releasing intrauterine system (LNG-IUS) has been advocated for the treatment of heavy menstrual bleeding as an alternative to surgery. Based on this established indication and theoretical potential of targeted endometrial solution of myoma-related bleeding, we evaluated the efficiency of LNG-IUS in treating selected cases presenting with heavy menstrual bleeding in the presence of uterine leiomyomas. This study included 68 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In contrast to this, Magal Haes et al found significant change in leiomyoma volume after 3 years. [14][15][16][17] Patients with anovulatory cycles suffer from loss of progesterone effect on the endometrium leading to proliferation of endometrium due to unopposed action of estrogen. Also, the recent theory suggests that the absence of progesterone results in reduced endometrial stromal cell factor, reduced plasminogen activator inhibitor-1 production, increased matrix metalloproteinase activity and increased angiogenic factor expression.…”
Section: -12mentioning
confidence: 99%
“…In contrast to this, Magal Haes et al found significant change in leiomyoma volume after 3 years. [14][15][16][17] Patients with anovulatory cycles suffer from loss of progesterone effect on the endometrium leading to proliferation of endometrium due to unopposed action of estrogen. Also, the recent theory suggests that the absence of progesterone results in reduced endometrial stromal cell factor, reduced plasminogen activator inhibitor-1 production, increased matrix metalloproteinase activity and increased angiogenic factor expression.…”
Section: -12mentioning
confidence: 99%
“…Several studies show no significant effect or a significant but small effect on fibroid volume. (Magalhaes et al 2007;Shawki et al 2009;Socolov et al 2011;Tasci et al 2009;Xie et al 2012; Lopez-Olmos 2016)…”
Section: Levonorgestrel Intra Uterine Devicementioning
confidence: 99%